Music‐making in the community with people living with dementia and care‐partners – 'I'm leaving feeling on top of the world'. (6th April 2021) - Smith, Sarah K.; Innes, Anthea; Bushell, Sophie
Abstract: Evidence exists relating to music‐based initiatives and positive health outcomes for people living with dementia who can access them. Yet, knowledge about the impact of 'music‐making' on the well‐being of community‐dwelling people with dementia is limited. Much of the existing evidence about the benefits of music is focused on care home settings where initiatives can be readily applied as part of a weekly schedule of activities. Therefore, this initiative aimed to provide opportunities to participate in music‐making, to increase social interaction and ultimately well‐being in a community environment. Ten music‐making session were scheduled for community‐dwelling people living with dementia and care‐partners, once a month between September 2019 and March 2020. Three sessions did not take place due to Covid19. Eighteen participants consented to take part including seven people living with dementia, five care‐partners and six former care‐partners. Baseline semi‐structured interviews explored the lived experience of music and expectations of the upcoming music‐making cafes. Self‐report questionnaires captured 'in the moment' experiences of each music‐making cafe. Follow‐up semi‐structured interviews explored the impact of music‐making on participants' self‐reported well‐being. Interviews were transcribed verbatim and analysed thematically. The findings demonstrate that participating in the music‐making café benefitted the self‐reported well‐being of participants in three ways: first, a sense of camaraderie that enabled the facilitation of connections with others; second, creating opportunities to 'level the playing field' by always assuming a person's strengths and abilities; and third, group participation in music‐making meets a need for meaningful musical experiences. We conclude that participating in music‐making is a powerful medium to promote well‐being for community‐dwelling people living with dementia and care‐partners.